Identification and genomic analysis of a novel temperate bacteriophage infecting Labrenzia aggregata isolated from the Mariana Trench - Gu, Bingyu; Wang, Haowen; Lv, Jiayi; Zheng, Yanfen; Zhang, Xiao-Hua; Zhan, Yuanchao (Frontiers in Marine Science, 2024)
In marine environments, viruses play a pivotal role, yet deep-sea bacteriophages remains largely uncharacterized. The bacterium Labrenzia aggregata RF14, isolated from the Mariana Trench at a depth of 4,000 meters, harbors prophage regions based on previous study. In this study, we induced a temperate bacteriophage from it using mitomycin C. The bacteriophage exhibited an icosahedral structure with a non-extendable tail and was named vB_LagS-V1. The genome size of it is 39,329 bps with a 59.46% G+C content, encoding 60 putative open reading frames. Genomic and phylogenetic analyses demonstrated that vB_LagS-V1 along with many bacteriophages infecting Hyphomicrobiales, constituted a newly unclassified family, which we designated as Hyphoviridae. Within this novel family, vB_LagS-V1 is distinct with isolated phages and clustered with two uncultured prophages within Labrenzia, forming an unclassified new genus, given a name of Labrenmarinevirus. The codon usage correlation and absence of tRNAs found in vB_LagS-V1, also prevail in some deep-sea bacteriophages, highlighting their adaptations to the deep-sea prokaryotic hosts. Moreover, vB_LagS-V1 encoded two auxiliary metabolic genes, cysteine dioxygenase and phosphoadenosine phosphosulfate, which might help the phage and its host adapt to high hydrostatic pressure in the deep-sea environments. Our study will significantly contribute to the understanding of deep-sea bacteriophages and their interactions with hosts in extreme environments.